Assessment of Safety Culture at a Veterinary Teaching Hospital in the United States - Love, Lydia C.; Hedgpeth, Mari-Wells; Robertson, James B.; Marks, Steven L.; Schoenfeld-Tacher, Regina M. (Frontiers in Veterinary Science, 2021)
This study assessed the fidelity of an existing questionnaire regarding attitudes towards safety culture in an academic veterinary hospital setting and gathered baseline data on these attitudes in a local population. A cross-sectional study design was used to evaluate perceptions held by veterinary teaching hospital employees. An established veterinary safety culture survey was modified and administered as a confidential online survey to faculty, house officers, and professional staff of a veterinary teaching hospital in the United States. Confirmatory and exploratory factor analysis were conducted to compare the adapted survey to the established version. Descriptive statistics were used to characterize baseline safety culture. The adapted survey exhibited factor groupings that were mostly in agreement with, but slightly different from, the original instrument. In general, survey respondents outlined positive attitudes towards the various domains of safety culture, though we identified opportunities for improvement in some areas. An adapted veterinary safety culture survey can be applied to a veterinary teaching hospital in the United States to assess baseline data surrounding the culture of safety and to identify opportunities for focused improvement efforts.